Monitoring the electrochemical transformation of an azobenzene-terminated alkanethiolate monolayer at gold by chemical force microscopy - Wu, Zhongyun (2013)
Chemical Force Microscopy (CFM) was used to study the electrochemical behavior of azobenzene-terminated self-assembled monolayers (SAMs). Both the gold-coated AFM tip and the gold-coated silicon substrate were modified with a 4-((N-(2′-mercapto-ethyl)-amino) carbonyl) azobenzene monolayer. For such a system, only when the reduction/oxidation reaction of azobenzene group occurs, the adhesion force between the tip and sample shows a drastic change, demonstrating the ability of CFM in monitoring the electrochemical transformation of an azobenzene group.